The limits of state interference with the distribution of wealth, in applying taxation to the assistance of the public - Longfield, Mountifort (Statistical and Social Inquiry Society of Ireland, 1872)
The science of political economy teaches the laws which regulate the creation, accumulation, and distribution of wealth. It has been fully proved that as soon as society arrives at a very moderate degree of civilization, the state can give very little assistance to the creation of wealth. It may even be said that its interference, in general, although with the best intentions, has been absolutely mischievous. More especially that interference, which by an abuse of the word is sometimes called protection, has constantly defeated its own object.
Read before the Society, 23 April 1872
Keywords: Income distribution; Government welfare policy; Wealth redistribution; 314.15